Exercise improves body composition, physical fitness, and blood levels of C-peptide and IGF-1 in 11- to 12-year-old boys with obesity - Ha, Min-Seong; Moon, Hyo Youl; Lee, Minchul; Yook, Jang Soo (Frontiers in Physiology, 2025)
IntroductionExercise is vital in preventing and treating obesity. Despite its importance, the understanding of how exercise influences childhood obesity at the biochemical level is limited. In this study, we explore the effects of a 16-week exercise program (EP) on body composition, physical fitness, and the blood levels of hormones related to obesity.MethodsSixteen boys with obesity (n = 16) and seventeen boys without obesity (n = 17) took part in an EP comprising sports games and aerobic and resistance exercises. We examined alterations in body composition and physical fitness. In addition, we measured circulating hormone levels, including C-peptide, resistin, insulin-like growth factor 1 (IGF-1), and growth hormone (GH), in the blood.ResultsBody fat percentage (BFP) decreased from 37.61% at pre-EP to 29.16% at post-EP in the obese group, but not in the non-obese group. The EP decreased C-peptide (4.58 ng/mL vs. 2.96 ng/mL, p < 0.001) and resistin levels (14.05 ng/mL vs. 11.06 ng/mL, p < 0.001) in the obese group. After the EP, significant improvement in IGF-1 (non-obese: 265.56 ng/mL vs. 311.81 ng/mL, p < 0.001; obese: 224.74 ng/mL vs. 272.89 ng/mL, p < 0.001) and GH levels (non-obese: 3.91 ng/mL vs. 4.80 ng/mL, p < 0.05; obese: 1.76 ng/mL vs. 2.51 ng/mL, p < 0.05) were observed in both groups. Lower C-peptide levels were associated with BFP (r = 0.447, p = 0.009) and muscle mass (r = −0.385, p = 0.02), whereas enhanced IGF-1 levels correlated with increased muscle strength (r = 0.343, p = 0.05) and cardiovascular fitness (r = 0.347, p = 0.04). Multiple linear regression analysis revealed that cardiovascular fitness variability and BFP in the obese group were determined by C-peptide (β = −0.054, p < 0.001) and IGF-1 levels (β = −2.936, p < 0.05), respectively.DiscussionExercise may induce positive effects on improvements in body composition and physical fitness, as well as on blood levels of metabolic biochemicals such as C-peptide and IGF-1, in adolescent boys with obesity.